Aplikasi Posyandu Berbasis Android Studi Kasus Puskesmas Mowbja - Saleh, Arif Fatur Rahman; Oktavia, Chaulina Alfianti; Anita, Anita (J-INTECH (Journal of Information and Technology), 2021)
Posyandu is a form of population-based health efforts that are managed and organized from, by, for and with the population in the implementation of health development, in order to empower the population and provide facilities for the population to obtain basic health services. However, all of these are not supported by good means of conveying information. The process of managing and registering is quite troublesome for cadres and midwives due to the obstacles they often encounter. The process is manual and inefficient, this can take a long time. In this research, an android posyandu application will be designed. The making of this application uses problem analysis and software design along with testing the software. The results of this study are in the form of monitoring and managing information kesehatan ibu dan anak (KIA).